Surface Analysis of Coal Indicating Neutral Red Enhances the Precursor Steps of Methanogenesis - Srivastava, Priyanka; Marjo, Christopher; Gerami, Alireza; Jones, Zackary; Rahman, Sheik (Frontiers in Microbiology, 2020)
Artificially-stimulated, high-yield microbial production of methane from coal is a challenging problem that continues to generate research interest. Decomposition of organic matter and production of methane from coal are the results of multiple redox reactions carried out by different communities of bacteria and archaea. Recent work by our group (Beckmann et.al., 2015) demonstrated that the presence of the redox-mediating molecule neutral red, in its crystalline form on a coal surface, can increase methane production. However, hydrolysis and the acetogenesis of the coal surface are essential precursor steps for methane production by archaea. Acetogenesis is the preparation phase of methanogenesis because methanogens can only assimilate acetate, CO2 and H2 among the products formed during this process. In the present study, the surface chemical analysis of neutral red treated coal using attenuated total reflectance-Fourier transform infrared (ATR-FTIR) spectroscopy and X-ray photoelectron spectroscopy (XPS) demonstrate that acetate production must occur at the nanoscale (<5 nm). We observed that in the presence of neutral red and groundwater microbes, acetate signals in coal surface chemistry increased. This is the first evidence suggesting that neutral red enhances the biological conversion of coal into acetate, consistent with its stimulation of methanogenesis. Microscopy demonstrated that neutral red crystals were co-localize with cells at the surface of coal in groundwater. This is consistent with neutral red crystals serving as a redox hub, concentrating and distributing reducing equivalents amongst the microbial community. In this study, the chemical changes of neutral red treated coal indicated that neutral red doubles the concentration of acetate over the control (coal without neutral red), emphasizing the importance of maximizing the fracture surface coverage of this redox mediator. Overall, results suggested that neutral red not only can benefit acetoclastic methanogens but also the fermentative and acetogenic bacteria involved in generating acetate.